Synthesis of Two Analogues of Xylapeptide A and Their Potency as New Antimicrobial Agent - Maharani, Rani; Muchlis, Handi Nugraha; Hidayat, Ace Tatang; Al-Anshori, Jamaludin; Nurlelasari, Nurlelasari; Harneti, Desi; Mayanti, Tri; Farabi, Kindi; Supratman, Unang (Universitas Gadjah Mada, 2025)
Xylapeptide A, derived from the fungus Xylaria sp. x Sophora tonkinensis, exhibits potent and selective antimicrobial properties. Our research group has successfully synthesized xylapeptide A. In our recent work, two xylapeptide A analogues (An1 and An2) were synthesized using a combination of solid- and solution-phase synthesis methods. The linear precursors of An1 and An2 were synthesized on 2-CTC resin with the Fmoc strategy. The coupling reagents HBTU/HOBt and HATU/HOAt were employed. Subsequently, the linear precursor was cleaved from the resin using either 20% TFA or a TFE mixture, and then cyclized in solution phase with HBTU. The synthesized products were purified using semi-preparative RP-HPLC, giving the percent yields 16% for An1 and 12% for An2. Both compounds were then characterized by HR-ToF-MS, 1H- and 13C-NMR. The synthesized xylapeptide A and its analogues were evaluated against Bacillus cereus, Bacillus subtilis, Staphylococcus aureus, Enterococcus faecalis, Escherichia coli, Klebsiella pneumoniae, and Candida albicans. The result showed that An2, possessing arginine residue, exhibited higher activity compared to xylapeptide A and An1. This research suggests that xylapeptide A analogues hold great promise as novel antimicrobial agents.